Weight and Height Growth of Children Age 14-23 Months Reviewed from Nutrition Intake - Izzah, Nelatul; Handayani, Sri Sularti Dewanti (BELIA: Early Childhood Education Papers, 2020)
Breast milk is the best food for babies. WHO recommends exclusive breastfeeding during the first 6 months of birth in infants. Breast milk contains all the substances that babies need. However, there are still babies who are not given exclusive breastfeeding and have never even felt breast milk. This is due to the mother's breastmilk not coming out, working mothers, or the production of breastmilk that is felt to be inadequate in meeting the needs of the baby. This study discusses the differences in growth focused on the weight and height of children aged 14-23 months who drink breast milk and infant formula. This type of research is a comparative study with cross sectional design. The population is 115 children aged 12-24 months in Sekaran village. As in this study, respondents are 30 mothers who have children aged 14-23 months. While the sample is 15 children who drink breast milk and 15 children who drink infant formula. The sampling technique uses purposive sampling, where the sample is selected according to predetermined inclusion criteria. Data collection is done through questionnaires, interviews, and documentation. Growth data is seen through KMS (health card), filling questionnaires, and interviews with respondents. Hypothesis testing uses an independent t test. The results showed that there are differences in body weight and height growth between children aged 14-23 months who are breastfeed and who take infant formula. The average weight growth value of children who drink breast milk is 10.94 and children who drink formula milk 11.83. The average height growth value of children who drink breast milk is 81.85 and children who drink formula milk 78.46. The difference in average body weight of children who drink breast milk with children who drink formula milk is 1.43. While the difference in the average height of a child who drinks milk with a child who drinks formula milk is 3.39.